Exploring the forensic effectiveness and population genetic differentiation in Guizhou Miao and Bouyei group by the self-constructed panel of X chromosomal multi-insertion/deletions - Xiaolan Huang; Changyun Gu; Qianchong Ran; Li Chen; Shunyi Tian; Min Zhong; Zheng Ren; Qiyan Wang; Meiqing Yang; Jingyan Ji; Wen Wan; Jiang Huang; et al. (BMC Genomics)
Abstract In this research, a self-developed panel comprising 22 X chromosomal multi-InDels and one X-STR was used to explore the genetic polymorphisms and forensic characteristics of these loci in Guizhou Miao and Guizhou Bouyei populations. Besides, genetic affiliations among Guizhou Miao, Guizhou Bouyei and Guizhou Han populations were investigated using principal component analysis, STRUCTURE and machine learning methods. The findings indicated that these loci in the male and female samples had comprehensive discrimination powers greater than 0.999999999. Meanwhile, the cumulative mean exclusion chance of these 23 loci for trio and duo cases were also greater than 0.9999 in Guizhou Miao and Guizhou Bouyei populations. Population genetic analyses of three Guizhou populations revealed that there were relatively low genetic divergences among these populations based on the self-constructed panel. In conclusion, this system could be utilized as the valuable tool for forensic personal identification and parentage testing in Guizhou Miao and Guizhou Bouyei populations.